Ascending axonal degeneration of the corticospinal tract in pure hereditary spastic paraplegia: A cross-sectional DTI study - List, Julia; Kohl, Zacharias; Winkler, Jürgen; Marxreiter, Franz; Dörfler, Arnd; Schmidt, Manuel (Brain Sciences, 2019)
Objective: To identify structural white matter alterations in patients with pure hereditary spastic paraplegia (HSP) using high angular resolution diffusion tensor imaging (DTI). Methods: We examined 37 individuals with high resolution DTI, 20 patients with pure forms of hereditary spastic paraplegia and 17 age and gender matched healthy controls. DTI was performed using a 3 T clinical scanner with whole brain tract-based spatial statistical (TBSS) analysis of the obtained fractional anisotropy (FA) data as well as a region-of-interest (ROI)-based analysis of affected tracts including the cervical spinal cord. We further conducted correlation analyses between DTI data and clinical characteristics. Results: TBSS analysis in HSP patients showed significantly decreased fractional anisotropy of the corpus callosum and the corticospinal tract compared to healthy controls. ROI-based analysis confirmed significantly lower FA in HSP compared to controls in the internal capsule (0.77 vs. 0.80, p = 0.048), the corpus callosum (0.84 vs. 0.87, p = 0.048) and the cervical spinal cord (0.72 vs. 0.79, p = 0.003). FA values of the cervical spinal cord significantly correlated with disease duration. Conclusion: DTI metrics of the corticospinal tract from the internal capsule to the cervical spine suggest microstructural damage and axonal degeneration of motor neurons. The CST at the level of the cervical spinal cord is thereby more severely affected than the intracranial part of the CST, suggesting an ascending axonal degeneration of the CST. Since there is a significant correlation with disease duration, FA may serve as a future progression marker for assessment of the disease course in HSP.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Corticospinal tract; Diffusion tensor imaging; Fractional anisotropy; Hereditary spastic paraplegia; Tract-based spatial statistics (TBSS)